Polarization and Rationality of Political Choices of the People of Padang City in the 2024 Presidential Election - M. Nursi (Publikasi Indonesia, 2024)
The 2024 Presidential Election (Pilpres) in Indonesia, including in West Sumatra and the City of Padang, is a strategic battle, not only in the context of heading towards a Golden Indonesia in 2045 but taking place in a unique configuration and axis of political power and ideology and development ideology, namely between the political ideology of Islamism with Nationalism, and between the development ideology